Probiotics in the Modern World - Y. P. Uspenskiy; Y. A. Fominykh; K. N. Nadzhafova; S. V. Polyushkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim of review. The review highlights modern concepts of the role of microbiome in sustaining the human body, the place of probiotics in treatment and prevention of pathologies related to disorders in healthy microbiota.Key points. Microbiome is a unique panorganismal system normally maintaining self-equilibrium and possessing a vast and diverse functionality. Imbalance in normal microbiota can be assisted by probiotics, i.e. living microorganisms that sustain health of the host when being supplied in adequate amounts. Alike normal microflora, probiotic strains incorporate into general metabolism by mediating a spectrum of functions, e.g. maintaining colonisation resistance, nutrient metabolism, supplying the host with vital metabolites, regulation of local and adaptive immune responses, enhancing the intestinal barrier. Probiotics are applied in various diseases associated with general imbalances of the organism. Modern probiotic preparations are characterised by acid- and antibiotic-resistivity and safety, thus being suitable for treating gut microbiome-associated disorders in various age groups.Conclusion. Probiotic strains, as well as medications designed on their basis, are widely applied and show good promise. Further research into their properties will advance the prospects of probiotic treatment.